Associaçoes comunitárias do meio rural : Um estudo de caso no centro oeste de Minas Gerais - Toledo, Carla (Mundo Agrario.)
This paper examines the association in a rural mining town in Brazil. The results belong to a master dissertationin Rural Extension on membership organizations and public policies for rural areas aiming to identify the roles performed by membership organizations, the reasons that explained their formation and their relationship with policy making for rural areas in the case studied. It is a case study, for which interviews were conducted with representatives of the organizations in order to deepen into the issues related to their historical, the roles they play and how and whether they participate in development project proposals. The results revealed anup-down process of formation of rural organizations, being created as bargaining tools for achieving collective benefits, reproducing dependency relationships